The Role of Stakeholders in Improving The Quality of Islamic Education in Madrasah Aliyah Nahdlatul Wathan Suela - Azwar, Chairul; Badrun, Badrun; Fadli, Adi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This research aims to determine stakeholder governance in improving the quality of education at Madrasah Aliyah Nahdlatul Wathan Suela. This governance includes the management of teaching staff and educational staff in improving the quality of secondary education at Madrasah Aliyah Nahdlatul Wathan Suela, management of students in improving the quality of secondary education at Madrasah Aliyah Nahdlatul Wathan Suela, governance of partner communities and graduate users in improving quality. secondary education Madrasah Aliyah Nahdlatul Suela. The methodology in this research uses a qualitative approach. Data collection techniques in this research include observation, in-depth interviews, document review. And visualization and representation of findings. The research results show that stakeholder governance in improving the quality of education at Madrasah Aliyah Nahdlatul Wathan Suela includes management of teachers and education personnel, student governance, and how the madrasah manages the role of stakeholders in improving the quality of secondary education. Education at Madrasah Aliyah Nahdlatul Wathan Suela is carried out very well so that the quality of education at Madrasah Aliyah Nahdlatul Wathan Suela is very good.